1970
DOI: 10.1136/jcp.23.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Elastic vascular sclerosis of mesenteric blood vessels in argentaffin carcinoma

Abstract: SYNOPSIS Argentaffin carcinoma (carcinoid tumour) of the ileum has been found to be associated with ischaemic ileal necrosis due to elastic sclerosis of the mesenteric blood vessels. This vascular change was present in 17 out of 25 ileal tumours, all of them invasive, but was absent in 75 appendicular, rectal, and other carcinoids. The pathology is described and essential points of difference are noted from the cardiovascular changes in the carcinoid syndrome. This elastic vascular sclerosis may be due to a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…A specific feature of ileal and jejunal well-differentiated endocrine tumours is the diffuse proliferation of both intimal and adventitial elastic tissue in large arterial and venous vessels of the mesenteric pedicle, often called vascular elastosis (Anthony & Drury 1970, Qizilbash 1977) and sometimes associated with proliferation of extravascular elastic fibres within the bowel wall (Qizilbash 1977). Not infrequently, vascular elastosis may cause ischaemic changes or even intestinal infarction.…”
Section: Potential In Vivo Effects Of Growth Factorsmentioning
confidence: 99%
“…A specific feature of ileal and jejunal well-differentiated endocrine tumours is the diffuse proliferation of both intimal and adventitial elastic tissue in large arterial and venous vessels of the mesenteric pedicle, often called vascular elastosis (Anthony & Drury 1970, Qizilbash 1977) and sometimes associated with proliferation of extravascular elastic fibres within the bowel wall (Qizilbash 1977). Not infrequently, vascular elastosis may cause ischaemic changes or even intestinal infarction.…”
Section: Potential In Vivo Effects Of Growth Factorsmentioning
confidence: 99%
“…In others the bowel was entrapped by tumor and fibrosis and appeared partly occluded, without proximal dilatation, but frequently with a localized intestinal edema. consisting of elastic tissue proliferation within the adventitia of mesenteric arteries and veins (17)(18)(19)(20). A compromised circulation was evident in the present series only in intestinal segments neighboring large mesenteric lymph node metastases, but has been described also in their absence and in intestinal segments remote from the tumors (17-20).…”
Section: Operative Findings and Surgical Strategymentioning
confidence: 63%
“…Mesenteric vascular elastosis is characterized by thick deposition of elastic tissue in the adventitia of mesenteric arteries and veins. 28 Some authors have suggested that mesenteric vascular elastosis associated with JINETs can cause IIN. 12,13,17,28 Finally, it is conceivable that decreased blood flow from preexisting cardiovascular disease, such as mesenteric arterial atherosclerosis, and decreased cardiac function could predispose to JINET-induced IIN.…”
Section: Commentmentioning
confidence: 99%
“…28 Some authors have suggested that mesenteric vascular elastosis associated with JINETs can cause IIN. 12,13,17,28 Finally, it is conceivable that decreased blood flow from preexisting cardiovascular disease, such as mesenteric arterial atherosclerosis, and decreased cardiac function could predispose to JINET-induced IIN. Although no significant differences in hypertension, dyslipidemia, diabetes, and smoking status were found between patients with and without IIN, age itself is a risk factor for atherosclerosis.…”
Section: Commentmentioning
confidence: 99%